NAVIGATING CEO HIRING: THE VALUE OF SPECIALIST CEOS FOR SUSTAINABLE SUCCESS IN CHINESE IPOS - G, Jiang (Economics and Statistics Research Journal (ESRJ), 2022)
This study investigates the impact of CEO personality and strategy on a company's post-IPO performance in the Chinese A-share market from July 2009 to July 2021. The study constructs a generalist skills index for CEOs based on work experience, and finds that companies with a specialist CEO have a higher probability of survival than those with a generalist CEO. The former category focuses on a long-term and sustainable approach to decision-making and is more devoted to the company's long-term survival. Performance-related compensation and CEO turnover further explain the higher probability of firm failure in companies with generalist CEOs, who pursue higher salaries and reputations through switching between different industries and firms. The study's empirical evidence is derived from the Cox proportional hazards model and robustness check. This research contributes to the literature by being the first to examine how a CEO's managerial expertise affects a company's ability to survive post-IPO in the Chinese stock market. The findings offer insights for companies in choosing a CEO based on their long-term goals